'Sandwiched' or 'filtering': middle leaders' agency in innovation enactment. Issue 3 (3rd May 2020) - Zhou, Jiming; Deneen, Christopher
ABSTRACT: University middle leaders play a significant role in change management. While research examines the outcomes of change management, far less attention has been paid to how middle leaders develop agency and negotiate their identities in achieving these outcomes. This study presents the cases of two middle leaders in Shanghai enacting a curriculum reform at their respective universities. Participants were interviewed at the beginning and the end of the first innovation year and relevant curriculum documents were collected. Data were analysed using a thematic analysis protocol. Figured worlds theory provides a conceptual lens for analysis. The two leaders demonstrated distinctly different patterns of response. Agency and negotiations strongly related to whether they saw themselves as 'sandwiched' between conflicting priorities or 'filtering' these priorities to produce meaningful outcomes. Implications for research and practice are discussed, including understanding and development of middle leaders' agency and identity in the face of complex innovation priorities.